Ownership V control: fault lines in directors shareholders relationship: a special reference to Malaysian family business - Hassan, Halyani; Abd Ghadas, Zuhairah Ariff (2009)

(untitled)
In an ideal corporate management structure, directors should act in the best interest of the shareholders. In doing so, the directors' actions are governed by certain legislation which specifies their duties and this legislation is also relevant to the shareholders with respect to their rights. Although there are legislations which govern the relationship between directors and shareholders, there are still latent problems. These hidden problems could be regarded as fault lines in the relationship of these two parties. In a family business structure, these fault lines could bring worse effect compared to “non-family” companies as the directors are dealings with shareholders who are also family members. Another arising scenario which could arise is where directors are not part of the family members but have to deal with shareholders/members who are related to the owner of the company. This paper intends to highlight the fault lines which could occur between directors and shareholder in family owned companies. The main term of reference of this paper is the corporate governance principles and practices. This paper also aims to propose some mechanisms, through legislations in which problems which arise from the fault lines could be reduce if not resolved.